Al-Mar’ah fi al-Qur’ân ‘Inda Ibn ‘Asyûr fi Tafsîrih (Dirâsah ad-Dilâlah al-Qur’âniyyah) - Ali Mahfuz Munawar; Dyah Nurul Azizah (Studia Quranika, 2017)
Al-Mar’ah in the Qur’an was one of the main discussions among Muslim scholars and mufassirin, either seen from the position level or the role of their life. There are various studies about Al-Mar’ah in the Qur’an, also the term that is used for the context of mar’ah, they are “imro’ah and nisa’. Centuries ago, a large number of orientalist placed the Qur’an as the main study, which had never been separated from jewish analogy. In fact, the most muslims had been incited by their digression of thought. So, the prominent Muslim scholar and the contemporary mufassir, Ibnu’Asyur tried to straighten the anconformity assumption of orientalist in accordance to the Divine Revalation of God and Islamic teaching. Ibnu ‘Asyur’s thought about “imro’ah and nisa” according to the semantic Qur’an study based on dalil naqly and aqly on his tafsir. Thus, the interpretation is very oriented to the study of language depth. The term "imroah and an-nisa" according to the interpretation described by Ibnu 'Asyur has a different meaning between them. The term "imroah" has a more specific meaning than "an-nisa", also devoted to the two writing styles, ta' ta'nits or ta 'maftuhah (امرأت) which is more oriented to have the meaning "wife" or idzofah on the name of her husband which is written afterwards, and the writing with ta 'marbuthoh (امرأة) is used for 4 types of mar'ah they are barren women, old women, widow, and unmarried women.While for term "an-nisa" is a plural form of "imroah" which is dissaproved from the ashlu-l-kalimah, on the meaning women or adult female.The term “an-nisa” is a general word which has no purpose into specific meaning, but has a variety of meanings such as wives, mothers, women menstruated, and others according to the context of the sentence in the verses.